Prediction of arterial blood gas values from venous blood gas values in Asiatic black bears (Ursus thibetanus) anesthetized with intramuscular medetomidine and zolazepam-tiletamine - JEONG, Dong-Hyuk (J Vet Med Sci, 2017)
The objective of this study was to measure differences between arterial and venous blood gas parameters and to evaluate whether arterial blood gas values can be estimated from venous blood in Asiatic black bears (ABBs). Twelve healthy captive ABBs (8 males and 4 females; 8–16 years; 76.8–220 kg) were included in this study. The bears were immobilized with medetomidine and zolazepam-tiletamine using a dart gun. Arterial and venous samples were collected simultaneously at 5 and 35 min after recumbency (5- and 35-min points). Partial pressure of oxygen (PO(2)), partial pressure of carbon dioxide (PCO(2)), pH, bicarbonate (HCO(3)(−)), total carbon dioxide (TCO(2)), oxygen saturation of hemoglobin (SO(2)) and base excess (BEecf) were analyzed using a portable blood gas analyzer. There was no marked difference in measured and calculated variables over time in both venous and arterial blood except for PO(2). However, arterial PO(2), SO(2) and pH were significantly higher and arterial PCO(2), TCO(2) and HCO(3)(−) were lower than those of venous samples at both 5- and 35-min points. In the regression analysis to estimate arterial values from venous values, PCO(2), TCO(2), HCO(3)(−), BEecf and pH significantly showed over 0.45 in coefficient of determination value (R(2)), and there were little differences between actual and predicted arterial values. Although there were limits in venous gas values replaced those of arterial blood, if we could not get the arterial samples, the regression formulas for arterial values from venous blood in this study would be useful clinically, except for PO(2) and SO(2).